2010
DOI: 10.1074/jbc.m110.104950
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of High Molecular Weight Hyaluronan (900 kDa) Controls Immune System via Toll-like Receptor 4 in the Intestinal Epithelium

Abstract: Low molecular weight hyaluronan enhances or induces inflammation through toll-like receptor 4 (TLR-4).However, the effects of high molecular weight hyaluronan (HA900) on TLR-4 are unknown. In this study, HA900 (900 kDa) was administered orally to MRL-lpr/lpr mice, a Th-1-type autoimmune disease model. Lymphoaccumulation of double-negative T cells, which is enhanced by proinflammatory cytokines, was suppressed by HA900 treatment. Cytokine array analysis showed that HA900 treatment enhanced production of interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 30 publications
3
56
0
1
Order By: Relevance
“…These results indicate that colitis can occur in mice lacking MDR1a; however, the pathogenesis of colitis is unrelated to the systemic immune response, and is possibly due to an abnormal local colonic epithelial cell barrier. Asari et al (2010) confirmed that MDR1a is the only P-gp gene expressed in mouse intestinal epithelial cells and intestinal lymphocytes and established an…”
Section: Introductionsupporting
confidence: 50%
“…These results indicate that colitis can occur in mice lacking MDR1a; however, the pathogenesis of colitis is unrelated to the systemic immune response, and is possibly due to an abnormal local colonic epithelial cell barrier. Asari et al (2010) confirmed that MDR1a is the only P-gp gene expressed in mouse intestinal epithelial cells and intestinal lymphocytes and established an…”
Section: Introductionsupporting
confidence: 50%
“…In addition, two previous studies have demonstrated TLR4-dependent mechanisms by which HA contributes to the integrity of the intestinal epithelium in mice (34,60). However, both of these studies utilized HA polymer preparations predominantly Ͼ500 kDa in size.…”
Section: Discussionmentioning
confidence: 98%
“…nTregs are another regulatory T cell subset that are thought to primarily arise in the thymus (13). HA was recently reported to promote IL-10 production in intestinal biopsies upon oral administration (14). However, to our knowledge, ECM components have not been implicated in the induction of regulatory T cells and there are no described roles for HA or CD44, the primary HA receptor, in TR1 biology.…”
Section: Foxp3mentioning
confidence: 92%